REAKSI POLA RENANG IKAN NILA TERHADAP TIRAI LISTRIK PADA SKALA LABORATORIUM - Mochamad Rudyansyah Ismail; Diniah Diniah; Mulyono S Baskoro (Fakultas Perikanan dan Ilmu Kelautan, 2015)
The purpose of this study is to determine the behavior of Tilapia to TELV-PDC gear. TLEV-PDC is modification of fishing gear for blocking and guiding the fish swimming. This study use experimental method. Sampling for The Study used behavior sampling method and continuous method for recording. The power source of this study was 6 volts, 18 volts, 30 volts and 45 volts in the aquarium for testing deterrence Tilapia juvenile and consumption sized. The results of this study indicated the response of Tilapia to TLEV PDC was fainted, hampered and changed the direction of swimming, and blockouts. TLEV-PDC can to support for fishing gear. It is function for guiding the fish in passive fishing gear (trap).